2012
DOI: 10.1021/ja303181m
|View full text |Cite
|
Sign up to set email alerts
|

Scope of the Palladium-Catalyzed Aryl Borylation Utilizing Bis-Boronic Acid

Abstract: The Suzuki-Miyaura reaction has become one of the more useful tools for synthetic organic chemists. Until recently, there did not exist a direct way to make the most important component in the coupling reaction, namely the boronic acid. Current methods to make boronic acids often employ harsh or wasteful reagents to prepare boronic acid derivatives and require additional steps to afford the desired boronic acid. The scope of the previously reported palladium-catalyzed, direct boronic acid synthesis is unveiled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 62 publications
(118 reference statements)
3
78
0
Order By: Relevance
“…5-Chloro-2-fluoropyridine and 3-chlorophenol were chosen as partners because previous methods (without ethylene glycol) were effective in borylating the phenol derivative in the first step followed by cross coupling the pyridine derivative in the second step, but attempts to reverse the order (borylation of the pyridine derivative) with the previously developed procedure proved ineffective, even when an increased Pd loading was used. 5 The ethylene glycol method developed herein has now been shown to be quite effective in borylating pyridine derivatives, with subsequent cross-coupling with the phenolic halide providing the desired product in one pot in 78-82% overall yield on a 1.5 mmol or 7.6 mmol scale (Table 2, entry 4). Additionally, it was shown that the methoxy-substituted pyridine was also effective in borylation, with subsequent cross-coupling with an aryl and heteroaryl halide (Table 2, entries 6 and 7).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…5-Chloro-2-fluoropyridine and 3-chlorophenol were chosen as partners because previous methods (without ethylene glycol) were effective in borylating the phenol derivative in the first step followed by cross coupling the pyridine derivative in the second step, but attempts to reverse the order (borylation of the pyridine derivative) with the previously developed procedure proved ineffective, even when an increased Pd loading was used. 5 The ethylene glycol method developed herein has now been shown to be quite effective in borylating pyridine derivatives, with subsequent cross-coupling with the phenolic halide providing the desired product in one pot in 78-82% overall yield on a 1.5 mmol or 7.6 mmol scale (Table 2, entry 4). Additionally, it was shown that the methoxy-substituted pyridine was also effective in borylation, with subsequent cross-coupling with an aryl and heteroaryl halide (Table 2, entries 6 and 7).…”
Section: Resultsmentioning
confidence: 95%
“…These studies indicated that heteroaryl substrates typically react more effectively when used as the electrophilic component of the cross-coupling and are therefore added to the reaction after the borylation of the first aryl halide is complete, as attempts to use the heteroaromatic substrate as the borylated component in the cross-coupling step often resulted in low yields or no reaction at all. 5 Additionally, the coupling of two heteroaromatic halides proved to be unsuccessful using the previous BBA one-pot method. To expand the utility of the current method, we applied the ethylene glycol conditions to borylate a series of heteroaromatic substrates and subsequently cross-coupled them in one pot with either an aryl or heteroaryl coupling partner (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under conditions that were determined using high-throughput experimentation, arylboronic acids and a variety of boronate ester derivatives were accessed directly from aryl chlorides under Pd catalysis (Scheme 3) [9]. Because isolation of the boronate ester is not necessary, this method allows in situ coupling of organoboron compounds that are potentially unstable toward isolation [10]. A large variety of functional groups are tolerated on the starting aryl chloride, including ester, nitrile, nitro, ketone, alcohol, amino, and trifluoromethyl groups.…”
Section: Improvements Toward Organotrifluoroborate Synthesismentioning
confidence: 99%